2009
DOI: 10.2337/db09-0432
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inhibition of Protein Kinase C β2 Attenuates Inducible Nitric Oxide Synthase–Mediated Cardiovascular Abnormalities in Streptozotocin-Induced Diabetic Rats

Abstract: OBJECTIVEImpaired cardiovascular function in diabetes is partially attributed to pathological overexpression of inducible nitric oxide synthase (iNOS) in cardiovascular tissues. We examined whether the hyperglycemia-induced increased expression of iNOS is protein kinase C-β2 (PKCβ2) dependent and whether selective inhibition of PKCβ reduces iNOS expression and corrects abnormal hemodynamic function in streptozotocin (STZ)-induced diabetic rats.RESEARCH DESIGN AND METHODSCardiomyocytes and aortic vascular smoot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 48 publications
3
41
0
5
Order By: Relevance
“…Diabetic mice were given intragastrically 1 and 3 mg/kg of L-NIL vehicle (i.e., distilled water) once daily since the date of wounding. The doses of L-NIL were chosen based on previously published data [17,18]. Nondiabetic control received distilled water intragastrically.…”
Section: Full-thickness Excisional Wound and Drug Administrationmentioning
confidence: 99%
“…Diabetic mice were given intragastrically 1 and 3 mg/kg of L-NIL vehicle (i.e., distilled water) once daily since the date of wounding. The doses of L-NIL were chosen based on previously published data [17,18]. Nondiabetic control received distilled water intragastrically.…”
Section: Full-thickness Excisional Wound and Drug Administrationmentioning
confidence: 99%
“…Furthermore, alteration of PKC by hyperglycaemia is another pathway associated with micro-and macro-vascular complications observed in diabetic experimental models and patients (Lee et al 1989;Nagareddy et al 2009;Geraldes and King 2010). Among the existing PKC isoforms, the βII PKC is preferentially increased in aorta from diabetic animals (Inoguchi et al 1992;Guo et al 2003) and recent published results suggested that inhibition of PKC-βII may be a useful approach for correcting abnormal cardiovascular alterations present in diabetes (Nagareddy et al 2009;Geraldes and King 2010).…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, increased cyclooxygenase-derived products such as PGH 2 and TxA 2 are found in experimental diabetes, which contribute to increased vascular contractility (Peredo et al 1999;Xavier et al 2003;Shi and Vanhoutte 2008) and impairment of endothelium-dependent relaxation (Tesfamariam et al 1989;Akamine et al 2006). Furthermore, alteration of PKC by hyperglycaemia is another pathway associated with micro-and macro-vascular complications observed in diabetic experimental models and patients (Lee et al 1989;Nagareddy et al 2009;Geraldes and King 2010). Among the existing PKC isoforms, the βII PKC is preferentially increased in aorta from diabetic animals (Inoguchi et al 1992;Guo et al 2003) and recent published results suggested that inhibition of PKC-βII may be a useful approach for correcting abnormal cardiovascular alterations present in diabetes (Nagareddy et al 2009;Geraldes and King 2010).…”
Section: Introductionmentioning
confidence: 97%
“…In mice and rat models, iNOS was shown to play a significant role in pathological mechanism of several diseases linked to inflammation [44]. This isoform takes part in the development of arterial hypertension, diabetes mellitus or myocardial infarction [12,23,30,44,53,59]. The isoform of eNOS is present in endothelial cells lining the lumen of both the arterial or venous blood vessels, as well as in capillaries and lymphatic vessels.…”
Section: Immunohistochemical Markers Of Endothelial Cellsmentioning
confidence: 99%
“…TEM7 appears to represent the gene encoding surface proteins of human tumour endothelia which are most frequently expressed [18]. Both the protein and mRNA of TEM7 result in an increased expression of various solid tumours in the endothelia, including carcinomas of the brain, breast, large intestine, lung [30] and in osteogenic sarcomas [14,18]. It provides an opportunity for TEM7-targeted anti-angiogenic therapy, as the physiological ligand of TEM7 and TEM7R, cortactin has been identified.…”
Section: Tumour Endothelial Markermentioning
confidence: 99%